EDUKASI DAN MANAJEMEN PENGELOLAHAN SAMPAH BERBASIS WEBSITE DAN MENGURANGI VOLUME SAMPAH DI KELURAHAN LIMAU MANIS, PADANG - Nur Khairiyah; Wahyu Permana Putra; Robi Maulana; Luqyana Najla; Resmi Darni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Based on the data of Indonesia National Plastic Action Partnership in 2020, about 67.2 million tons of garbage in Indonesia are still left off every year. Garbage problem from year-to-year still have not been taken seriously by the government. A way in decreasing the volume of garbage is by building temporary waste storage. Sadly, some of the Indonesian temporary waste storage are not working properly. Not to mention the temporary waste storage in Limau Manis Selatan. Therefore, an education, socialization and training are needed. The main goal of this project is to minimalize the amount of waste with the help of information technology based website, to serve informations to the waste bank in Limau Manis Selatan. By creating this waste management app, people in there will feel the ease to manage their waste, and become more aware of the importance of proper waste handling. From this activity, satisfying result was obtained. People in the community start building a good habits, from sorting the trash based on the variety, building aquaponics, and maggots cultivation in terms of reducing the waste volume. Keywords: Information technology, website, waste management.